Development Of Zeolites-Based Catalysts For Hydrocracking Of Gas Oil. - H. Hameed, Bassim; Zakaria, Ridzuan (Universiti Sains Malaysia, 2008)

(untitled)
In this project, USY zeolite supported NiMo, CoMo, NiW and CoW were prepared using the incipient wetness method. Over NiWIUSY catalyst, the total conversion and distillate fuels were 15.54 and 15.77 wt%, respectively higher than those obtained over unloaded USY zeolite. Then NiWIUSY catalyst with different nickel and tungsten loadings were prepared. It was observed that at tungsten and nickel loadings of 23 and 5 wt%, the total conversion and yield of total distillate fuels were 63.35 and 52.35 wt%, respectively.